1987
DOI: 10.1148/radiology.162.2.3797675
|View full text |Cite
|
Sign up to set email alerts
|

Aged venous thrombi: radioimmunoimaging with fibrin-specific monoclonal antibody.

Abstract: Radioimmunoimaging of fresh canine venous thrombi with a murine monoclonal antibody specific for human and dog fibrin has been reported. Successful imaging of canine deep venous thrombi 1, 3, and 5 days old at the time of antibody injection is reported. Images were positive in all dogs, and the uptake of fibrin-specific antibody was equivalent to that of fresh thrombi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Thus, the generation of a mAb that can distinguish fibrin clots from fibrinogen, soluble fibrin, and D-dimer represents a major breakthrough because these proteins share common amino acid sequences. The specificity of the 102–10 mAb differed from existing anti-fibrin mAbs (NYB-T2G12223 and MH-120), as the 102–10 mAb reacted only with fibrin clots (Supplementary Fig. 1b).…”
Section: Resultsmentioning
confidence: 92%
“…Thus, the generation of a mAb that can distinguish fibrin clots from fibrinogen, soluble fibrin, and D-dimer represents a major breakthrough because these proteins share common amino acid sequences. The specificity of the 102–10 mAb differed from existing anti-fibrin mAbs (NYB-T2G12223 and MH-120), as the 102–10 mAb reacted only with fibrin clots (Supplementary Fig. 1b).…”
Section: Resultsmentioning
confidence: 92%
“…The critical question is how much aging? Radioimmunoimaging with a fibrin-specific monoclonal antibody showed that the concentration in fresh and up to 5 day-old thrombi were comparable 36. Molecular MR imaging of fibrin provides more detailed information on this; signal enhancement occurs in fresh thrombus and declines as the age of thrombus past 4 weeks 37.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the production of a monoclonal antibody that can distinguish a fibrin clot from fibrinogen, soluble fibrin, and D-dimer would be a major breakthrough because all of these substances have common amino acid sequences. The specificity of 102-10 IgG differs from existing anti-fibrin antibodies (i.e., NYB-T2G1 21 22 and MH-1 23 ), and as a result of its unique properties, it is not neutralized by fibrinogen, soluble fibrin, or D-dimer in the bloodstream. The amino acid sequence of the epitope of 102-10 IgG is completely conserved in mammals, birds, amphibians, and fish (Basic Local Alignment Tool, BLAST).…”
mentioning
confidence: 92%